Indigenous Microbiota Protects against Inflammation-Induced Osteonecrosis. (June 2020) - Williams, D.W.; Vuong, H.E.; Kim, S.; Lenon, A.; Ho, K.; Hsiao, E.Y.; Sung, E.C.; Kim, R.H.
Medication-related osteonecrosis of the jaw (MRONJ) is a rare intraoral lesion that occurs in patients undergoing long-term and/or high-dose therapy with nitrogen-containing bisphosphonates, a RANKL inhibitor, antiangiogenic agents, or mTOR inhibitors. The presence of pathogenic bacteria is highly associated with advanced stages of MRONJ lesions; however, the exact role of indigenous microbes in MRONJ development is unknown. Here, we report that the normal oral flora in mice protects against inflammation-induced osteonecrosis. In mice that developed osteonecrosis following tooth extraction, there was increased bacterial infiltration when compared with healed controls. Antibiotic-mediated oral dysbiosis led to a local inhibition of bone resorption in the presence of ligature-induced periodontitis (LIP). There was no significant difference in empty lacunae, necrotic bone formation, osteoclast number, and surface area in antibiotic-treated as compared with conventionally colonized mice following extraction of healthy teeth after zoledronic acid infusions. However, extraction of LIP teeth led to increased empty lacunae, necrotic bone, and osteoclast surface area in antibiotic- and zoledronic acid–treated mice as compared with conventionally colonized mice. Our findings suggest that the presence of the indigenous microbiota protects against LIP-induced osteonecrosis.